"\\displaystyle\n\ny\\mathrm{d}x + \\frac{x\\mathrm{d}y}{(x+y)^2} + \\mathrm{d}y = 0\\\\\n\n\n\\textsf{Multiplying through by}\\, (x + y)^2\\\\\n\ny(x + y)^2\\mathrm{d}x + x\\mathrm{d}y + (x + y)^2\\mathrm{d}y = 0\\\\\n\n\ny(x + y)^2\\mathrm{d}x + (x + (x + y)^2)\\mathrm{d}y = 0\\\\\n\nM = y(x + y)^2\\\\\n\n\\begin{aligned}\nM_y = \\frac{\\partial M}{\\partial y} &= (x + y)^2 + 2y(x + y)\\\\\n&= (x + y)(x + y + 2y)\\\\\n&= (x + 3y)(x + y)\n\\end{aligned}\\\\\n\nN = x + (x + y)^2\\\\\n\nN_x = \\frac{\\partial N}{\\partial x} = 1 + 2(x + y)\\\\\n\n\\textsf{Since}\\, N_x \\neq M_y,\\, \\textsf{the differential equation}\\\\\n\\textsf{is not exact.}"
Comments
Leave a comment